Fuel i.e. petrol, flow rehomogenizing method for internal combustion engine of motor vehicle, involves injecting fluid compound in primary intake duct to block rotation generated by air intake or recover fuel jets produced by fuel injectors - DECHAUME DAVID; DOGNIN CAROLINE (2009)
The method involves injecting a fluid compound e.g. methane, in a primary intake duct (2) by fluid compound injectors (10) for blocking rotation generated by intake of air or recovering fuel jets (18) produced by fuel injectors placed in the duct. The compound is injected on both sides of the fuel jets, and the fluid compound injector is placed in a bend so as to project a fluid compound jet (11) in an axial manner in the intake duct, where the bend is formed by the intake duct and a main duct. L'invention permet de remédier aux différentes turbulences et tournoiements de l'air dans le circuit d'admission d'un moteur à combustion interne. Il consiste à utiliser la projection d'un ou de plusieurs jets de composé fluidique (11), non loin des points d'injection de carburant (6) dans les conduits primaires d'admission (2), en amont des conduits d'admission (3). Application au circuit d'admission des moteurs à combustion interne.